Assessment of potentially toxic metal (PTM) pollution in mangrove habitats using biochemical markers: A case study on Avicennia officinalis L. in and around Sundarban, India. (August 2018) - Bakshi, Madhurima; Ghosh, Somdeep; Chakraborty, Debarati; Hazra, Sugata; Chaudhuri, Punarbasu
Abstract: Spatial distribution of potentially toxic metals (PTMs) and their accumulation in mangrove Avicennia officinalis L. were studied along 8 locations in and around Sundarban mangrove wetland, India. Among 8 locations, S3 (Chemaguri) and S5 (Ghushighata) showed higher concentration of PTMs (Cd, Cr, Cu, Ni, Pb, Zn) characterized by higher enrichment factors (3.45–10.03), geo-accumulation indices (0.04–1.22), contamination factors (1.14–3.51) and pollution load indices (1.3–1.45) indicating progressive deterioration of estuarine quality and considerable ecotoxicological risk. Metal concentration in A . officinalis leaves showed significant correlation with sediment metals implying elevated level of bioaccumulation. Significant statistical correlation between photosynthetic pigments (Chlorophyll a, Chlorophyll b), antioxidant response (free radical scavenging and reducing ability) and stress enzymatic activity (Peroxidase, Catalase, Super-oxide dismutase) of A . officinalis with increasing metal concentration in the contaminated locations reflects active detoxification mechanism of the plant. The study indicates the potentiality of biomonitoring metal pollution using studied biochemical markers in mangrove habitats. Highlights: Accumulation of potentially toxic metals in sediment and mangrove S3 & S5 show deteriorating sediment quality with considerable ecotoxicological risk. Correlation of photosynthetic pigment, antioxidative & stress enzyme activity with toxic metals Studied biochemical markers can be used to assess metal pollution in mangrove habitat.